Continuous training of teachers from the perspective of inclusion with students with autism spectrum disorder (Revista Internacional de Formação de Professores, 2022)
This article aims to analyze the continuing education of teachers who work with students with Autism Spectrum Disorder (ASD) in common classes in regular schools in the public school system of the Distrito Federal. It starts from international conventions, legislation on special education in order to extract scientific productions and conceptions about continuing teacher education from the perspective of school inclusion with ASD students. The result showed that the continuing education of teachers from the perspective of inclusion is anchored in current public policies and that, contradictorily, address elements with practical pedagogical practices and enable perspectives of training that advance in the immediate/mediate relationship. Therefore, the importance of expanding continuing education linked to the emancipatory, libertarian and autonomous process.
Keywords: Education. Continuing teacher education. Inclusion. Autism.